2019
DOI: 10.26710/rope.v1i1.1133
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Effect of Insurgency on Cowpea (Vigna Spp) Production in Potiskum Local Government Area of Yobe State, Nigeria

Abstract: This study analyzed the effect of insurgency on cowpea production in Potiskum Local Government Area of Yobe State, Nigeria. This study is quantitative research where 120 cowpea farmers were randomly interviewed using structured response questionnaires. Data were analyzed using descriptive and inferential statistics. The results showed that 35% of the respondents fell within the age bracket of 28-33 years; males constituted 55% and 42% had primary education. The findings further reveaed that 77.50% perceived th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results showed that the Boko Haram insurgency had taken a toll on all regular human activities in the area, including farming, at first (2012)(2013)(2014)(2015)(2016), to the point that agricultural and animal production almost came to a halt, and several farmers fled and became refugee for two years (2014)(2015)(2016). Usman and Bawa [2019] examined the impact of the insurgency on cowpea production in the Potiskum Local Government Area of Yobe State, Nigeria, which was investigated in this research work. 120 cowpea farmers were randomly sampled using structured answer questionnaires in this quantitative study.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The results showed that the Boko Haram insurgency had taken a toll on all regular human activities in the area, including farming, at first (2012)(2013)(2014)(2015)(2016), to the point that agricultural and animal production almost came to a halt, and several farmers fled and became refugee for two years (2014)(2015)(2016). Usman and Bawa [2019] examined the impact of the insurgency on cowpea production in the Potiskum Local Government Area of Yobe State, Nigeria, which was investigated in this research work. 120 cowpea farmers were randomly sampled using structured answer questionnaires in this quantitative study.…”
Section: Empirical Reviewmentioning
confidence: 99%